Quality Characteristics of Oyster Mushroom (Pleurotus flabellatus) Dried under Poly House - Chandra, S; Samsher, Samsher (Journal of Agricultural Engineering, 2003)
Experiments were conducted to investigate the effect of various pretreatments and poly house drying on quality characteristics of oyster mushrooms (P. flabellatus). Each sample was dehydrated from an initial moisture content of 1011% (db) to the final moisture content of 11% (db). Results indicated that the entire dehydration process took place in falling rate period. The temperature in poly house drier ranged from 20-50degree C against ambient temperature of 12-30degree C during the study. The untreated samples exhibited higher rehydration ratio before and after storage followed by those steeped and those blanched plus steeped. Mushroom samples pretreated with combination of blanching plus steeping in KMS (0.50%) and citric acid (0.25%) solution scored highest sensory score for colour, texture, flavour and overall quality.